Stewardship vs. Stagnation: An Empirical Comparison of Small Family and Non‐Family Businesses* - Miller, Danny; Le Breton‐Miller, Isabelle; Scholnick, Barry (Journal of Management Studies, 2008)
abstract Two major perspectives can be construed in the literature concerning the nature of family owned businesses (FOBs). The first implies that these enterprises have unique characteristics of stewardship. FOB owners are said to care deeply about the long‐term prospects of the business, in large part because their family's fortune, reputation and future are at stake. Their stewardship is said to be manifested by unusual devotion to the continuity of the company, by more assiduous nurturing of a community of employees, and by seeking out closer connections with customers to sustain the business. The second perspective is less flattering. It proposes that FOBs are unusually subject to stagnation: they are said to face unique resource restrictions, embrace conservative strategies, eschew growth, and be doomed to short lives. This paper develops and examines the merits of the two perspectives, neither of which has been systematically articulated or researched. It does so in an empirical study of only small firms that are owned and managed by their founder. Within this sample, it compares firms that are FOBs, that is, family owned and managed, with non‐FOBs, that is, owned and managed by a founder with no other relative involved in the business. The findings show significant support for all three aspects of the stewardship perspective of FOBs, and no support for any elements of the stagnation perspective.